Development of inhalable Erlotinib-Loaded Polymeric Micelles for Treatment of Non-Small Cell Lung Cancer: an in Vitro Study - Sulaiman S. Alhudaithi; Raisuddin Ali; Sarah O. Abaalola; Taghreed H. Altoum; Alhassan H. Aodah; Sarah M. Almufadhili; Nasser B. Alsaleh; Rawan Fitaihi; Ziyad Binkhathlan (Journal of Pharmaceutical Innovation, 2026)

MOF derived ZnO nanostructures modified with CoW12-polyoxometalates for enhanced sunlight driven degradation of methylene blue, ofloxacin and their mixtures - Nitin A. Tupsamindar; Arun S. Chopade; Sagar A. Chaudhari; Abhijit N. Kadam; Sandip R. Sabale; Vaishali Patil; Mohaseen S. Tamboli; Raisuddin Ali; Nguyen Tam Nguyen Truong; Vashishtha M. Gurame; Dattakumar S. Mhamane; Vijaykumar P. Ubale; et al. (Journal of Water Process Engineering, 2025)

P09-35: Aggravation of toxic effect of bisphenol A via oxidative and endoplasmic reticulum stress in the liver of obese female rats - A. Mangla; P. Goswami; S. Ahmad; S. Raisuddin (Toxicology Letters, 2023)

Kryptolebias marmoratus (Poey, 1880): a potential model species for molecular carcinogenesis and ecotoxicogenomics - J.‐S. Lee; S. Raisuddin; D. Schlenk (Journal of Fish Biology, 2008)
Kryptolebias marmoratus ( Rivulus marmoratus till 2004, order Cyprinodontoformes; family Rivulidae) is the only known self‐fertilizing hermaphrodite vertebrate. Because of this uniqueness, there has been great interest in its biology, physiology, developmental biology and genomics along with other basic and applied areas of environmental genomics and molecular carcinogenesis. In laboratory studies, K. marmoratus has shown susceptibility to a number of xenobiotics including carcinogens. Toxicologists are interested in the mechanisms of action of environmental chemicals of contemporary interest such as endocrine disruptors and may consider this as a suitable fish model for the study of chemically induced carcinogenesis. Single short‐term exposure to model chemical carcinogens is sufficient to induce tumourigenesis in K. marmoratus in a relatively short time span. In recent years, considerable data have been generated about gene sequences of K. marmoratus . Laboratory maintenance of K. marmoratus is relatively easy. Gene bank data are readily available, though not as extensive as for zebrafish Danio rerio or Japanese madaka Oryzias latipes . The expressed sequence tag (EST) data, differential display real‐time reverse‐transcriptase polymerase chain reaction and Gene Sequencer 20™ sequencing data have recently been helpful in understanding the genomics and proteomics of this species. Recently, sequences of the oncogene, ras , and tumour suppressor gene, p53 , have been reported in K. marmoratus . The expression of these important genes that play significant roles not only in carcinogenesis but also in other signal transduction pathways was observed to be modulated by environmental endocrine‐disrupting chemicals. Having a large sequence database (cDNA sequences and ESTs), it is expected that the use of a microarray in the near future will open new vistas for this fish with applications in cancer research, aquatic toxicology, endocrinology and genomics. This review discusses potential uses of K. marmoratus in new biotechnological approaches of aquatic toxicology.

Preexposure to Copper Modulates Nonenzymatic Antioxidants in Liver of Channa punctata (Bloch) Exposed to the Herbicide Paraquat - S. Parvez; S. Raisuddin (Bulletin of Environmental Contamination and Toxicology, 2006)

Heat stress‐induced alterations of antioxidants in the freshwater fish Channa punctata Bloch - M. Kaur; F. Atif; M. Ali; H. Rehman; S. Raisuddin (Journal of Fish Biology, 2005)
The effect of elevated temperature on the antioxidants in the freshwater fish Channa punctata was investigated. Fish stressed with an elevated temperature of 12° C, range ± 1° C over the ambient temperature for 3 h showed a significant ( P P P

Modulatory Effect of Cadmium Exposure on Deltamethrin-Induced Oxidative Stress in Channa punctata Bloch - F Atif; S Parvez; S Pandey; M Ali; M Kaur; H Rehman; H A Khan; S Raisuddin (Archives of Environmental Contamination and Toxicology, 2005)

Modulatory Effect of Cadmium Injection on Endosulfan-Induced Oxidative Stress in the Freshwater Fish, Channa punctata Bloch - F. Atif; M. Ali; M. Kaur; H. Rehman; S. Raisuddin (Bulletin of Environmental Contamination and Toxicology, 2005)

Inhibition of Brain Na + ,K + -ATPase Activity in Freshwater Catfish ( Channa punctatus Bloch) Exposed to Paper Mill Effluent - I. Sayeed; I. Ahmad; M. Fatima; T. Hamid; F. Islam; S. Raisuddin (Bulletin of Environmental Contamination and Toxicology, 2000)

Inhibition of Brain Na+,K+-ATPase Activity in Freshwater Catfish (Channa punctatus Bloch) Exposed to Paper Mill Effluent - I. Sayeed; I. Ahmad; M. Fatima; T. Hamid; F. Islam; S. Raisuddin (Bulletin of Environmental Contamination and Toxicology, 2000)

Responses of Circulating Fish Phagocytes to Paper Mill Effluent Exposure - I. Ahmad; M. Fatima; M. Athar; N. Z. Khan, S. Raisuddin (Bulletin of Environmental Contamination and Toxicology, 1998)